Analysis of Mining-Induced Delayed Surface Subsidence - Krzysztof Tajduś (MDPI AG, 2021)
The topic of residual subsidence is important in Europe as it defines possible surface deformation for closed mine areas. It has to be determined because of potential financial claims and damages of sensitive objects such as satellite dishes, precision mechanics objects, agriculture, forestry and hydrogeology, etc. Analyses of measured subsidence after the end of mining exploitation indicate that this process can last from several months to several dozen or even several hundred years, and the final surface subsidence is not known. It is dependent on the individual’s features of excavated medium, depth of exploitation, a system of exploitation, behaviour of surrounding rock masses, etc. In the article, the authors analysed the assessment of the subsidence process after the end of mining operations, based on the innovative method. This concerns the duration of the subsidence process and the size of the expected subsidence. The methodology was applied to the RAG Aktiengesellschaft company project where prognostic calculations were made for seven closed coal mines using unique results of precise height measurements carried out for more than 90 years by the German State Office for National Measurements (Landesvermessungsamt NRW) under the so-called levelling measurements net. These measurements are carried out every 2 years and serve to keep the altitude network in the whole state of Rhineland Westphalia up-to-date. The result of the prognosis for one case study, German mine Auguste-Victoria, is presented in the article.